2011
DOI: 10.1007/s11695-011-0555-2
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years Experience of Banded Gastric Bypass: Does It Make a Difference?

Abstract: Many surgeons support some sort of restriction of the gastric pouch outlet by placing a ring around the gastric reservoir. Previous studies have shown positive results of banded gastric bypass (BGBP); however, there are not many comparative long-term studies to assess the real advantage of placing a ring during gastric bypass (GBP) surgery. This study aims to evaluate the long-term outcome of patients subjected to BGBP and nonbanded GBP procedures. We studied 260 retrospective, nonrandomized obese patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…Heneghan et al [14] reported statistically superior weight loss in the banded group at 24 months, and in a sub-group analyses of this study, the authors show that superobese patients (BMI > 50) had even more benefit in terms of %EWL. Another study [17] showed that 10 years following surgery, the banded group achieved 81.7 %EWL compared to 62.3 %EWL in the non-banded group. Data from this study show (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heneghan et al [14] reported statistically superior weight loss in the banded group at 24 months, and in a sub-group analyses of this study, the authors show that superobese patients (BMI > 50) had even more benefit in terms of %EWL. Another study [17] showed that 10 years following surgery, the banded group achieved 81.7 %EWL compared to 62.3 %EWL in the non-banded group. Data from this study show (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Emesis was found to be higher in banded patients compared to non-banded patients, though these were treated conservatively which was successful without requiring any intervention. Awad et al [17] reported 3 band migrations (out of 260 banded surgeries) with a polytetrafluoroethylene (PFTE) ring in the beginning of their study. White et al [5] reported a higher reoperation rate of 27 % of which 7 % were ring removals after silastic ring Roux-en-Y gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…BGBP is as effective as BPD-DS for weight loss and maintenance [104]. Weight loss peaks around 18-24 months after the procedure with maintenance of 70.0-80.0% EWL reported at 4-12 years of follow-up [97,104,105] and significant TBWL of 32.5% [106]. There is slightly better resolution of T2DM and hypertension with BGBP associated with its higher long-term weight loss and maintenance [105].…”
Section: Indications/contraindications Weight Loss Diabetesmentioning
confidence: 94%
“…Typically, the excellent initial weight loss nadir is followed by 5.0-20.0% EW regain; however, RYGBP weight loss ≥ 50.0% is typically maintained over the long term. In studies 10-year follow-up, T2DM resolves in 50.0-80.0% of RYGBP patients, depending on the severity and duration of disease [96,97], an undeniable attribute of bariatric surgery that caused the American Diabetes Association (ADA) to recommend it in their treatment algorithm [93]. Importantly significantly by 40.0%, particularly deaths from heart disease, T2DM, and cancer [98].…”
Section: Indications/contraindications Weight Loss Diabetesmentioning
confidence: 99%
“…No other single study reports 10-year results with the rigour of the SOS; however, a recent meta-analysis of pooled data does confirm that weight loss from Roux-en-Y gastric bypass is maintained long-term [9]. There has been interest in improving the efficacy of the bypass by application of a prosthesis around the anastomosis ("banded gastric bypass") but current data are conflicting [10,11]. Finally, it appears quite clear that both weight loss and disease remission from gastric bypass are inferior to those from BPD with DS [12,13]; these benefits must be balanced with the greater technical demands, intense nutritional follow-up and potential for serious metabolic complications that are inherent to the DS.…”
Section: Does Bariatric Surgery Provide Sustained Weight Control?mentioning
confidence: 99%